Spiritual and Educational Culture and Education of Young People - M. Mamayunusova (Periodica Journal, 2023)
In the article, the reforms implemented in the field of spiritual and educational work in our country in the following years, some urgent issues of youth education and upbringing and spiritual culture were discussed.
Keywords: Uzbekistan; spiritual and educational reforms